RATIONALIZING THE PROPHETIC TRADITION: Muhammad al-Ghazâlî’s Ethical Hermeneutics of the Sunnah - Lutfi Rahmatullah; Ahmadi Fathurrohman Dardiri (Ulul Albab: Jurnal Studi Islam, 2025)
The publication of al-Sunnah al-Nabawîyyah bayna Ahl al-Fiqh wa Ahl al-Hadîth (1989) by Muhammad al-Ghazâlî sparked major controversy in the modern Islamic intellectual landscape due to its bold critique of the prevailing tendency toward literalism in the understanding of hadith. The central problem underlying al-Ghazâlî’s thought is the dominance of a textualist approach that rejects rationality and ethical considerations in interpreting the Prophet’s Sunnah. Hadith literalism, he argues, has distanced Islamic teachings from the moral spirit and contextual sensitivity inherent in the objectives of the maqâsid al-sharî‘ah. The present study aims to trace the rational and ethical foundations of Muhammad al-Ghazâlî’s methodology of hadith criticism, and to understand the socio-historical conditions that shaped his views on the relationship between the Quran and the Sunnah. Employing a qualitative research design, this study relies on library-based inquiry into al-Ghazâlî’s primary works and relevant secondary literature. It further applies an ethical-hermeneutical approach to uncover the moral orientation underlying his critique of the literalist tendencies within ahl al-hadith. The findings indicate that Muhammad al-Ghazâlî proposes a dynamic interpretive methodology for hadith interpretation grounded in reason, ethics, and contextual relevance, as part of an effort to revitalize the authority of the Sunnah so that it remains vibrant and capable of engaging with the challenges of modernity. This article contributes to contemporary hadith studies by situating Muhammad al-Ghazâlî’s critique within ongoing debates on literalist interpretation and by reconstructing a more rational and ethically attuned understanding of hadith. By highlighting al-Ghazâlî’s epistemological approach, which evaluates the substance of hadith in light of Quranic values, the study enriches methodological discourse and underscores the dynamic role of the sunnah and its relevance for modern Muslim life.